Management Development in Asia: An Exploratory Study on Malaysia-Based MNCs - Liau, Phui San (2007)
The unrivalled economic development in East Asia, led by Japan in the 1950s and followed first by the four Newly Industrialised Countries (South Korea, Taiwan, Hong Kong and Singapore) in the 1960s, then major ASEAN members in the 1970s and finally by China in the 1980s, had captured the interest of academics, policy-makers and business executives in the West. In the early 1990s, it seemed that East Asian growth has managed to maintain it momentum despite the economic downturn in the USA, Europe and Japan. Major reasons for this rise of independent momentum of growth in the global economy include massive infrastructural development projects; rising domestic purchasing power as a result of employment expansion and wage increases as well as a rapidly expanding middle-class; substantial expansion in private investment, rising interdependence in direct foreign investment; and intraindustry trade flows among the regional economies. No longer a mere wagon latched to the locomotive of US and European economies, East Asia becomes an attractive destination for both direct exports as well as direct investment targeting local and/or regional sales. It also provided fund managers in the OECD (Organisation for Economic Co-operation and Development) countries an alternative for asset diversification and higher returns (Tan, 1997).